She will be queen - Marinelli, Carol (Marinelli, Carol. Wed into a billionaire's world, 2024)
Claimed by the man, crowned by the king? Future king Sahir is required to marry for duty, not emotion. But after an unforgettably raw night with beautiful stranger Violet, he craves more. Then they're caught on camera and Violet is whisked straight to the desert for royal damage control! Violet is infuriated...especially by her body's traitorous response to being isolated with the only man who's ever touched her. Sahir's proximity is pure, delicious torture. For Violet knows her family's checkered past means she's not queen material, unless their deepening connection can convince Sahir to rip up his kingdom's rule book...